The bishop as a minister of blessings. A legal and liturgical analysis - Saj, Marek (Prawo Kanoniczne, 2018)
In the Code of Canon Law 1983 the lawmaker ennumerates consecrations, sacrifices and blessings amongst sacramentals. Practice of Christian life shows that blessings are the most commonly conducted. A person, an object or a place can be a subject of blessing. Each blessing has its own minister or ministers strictly established. It can be one clergyman, particularly designated, or it can be more in charge, for example a bishop, a presbyter, a deacon. Amongst numerous blessings there are those which, according to liturgical books, are reserved for bishop as their minister. In general, a bishop can be a minister of each blessing on the basis of the overall power he has over his particular church. But, there are blessings reserved to bishop only, and there are those which demand from bishop to be their minister. What is also important in this issue is the basis on which it is bishop who is to be a proper minister of particular blessings. We speak of basis of the aforementioned regulations. These issues, hence, are the subject of this analysis.